El turismo comunitario como herramienta de desarrollo de los pueblos indígenas: interrogantes en el caso de los shuar del Alto Nangaritza (Ecuador) (2020)
In this article we analyze community-based tourism as a potential development instrument for local populations. Since the 1980s, some indigenous groups in Ecuador have launched various community-based tourism initiatives. After making a lengthy anthropological fieldwork in the area Alto Nangaritza (Ecuador), our objective is to show the contradictions that community-based tourism represents for local populations, specifically for the Shuar communities in the region. Faced with a tourism that aims to empower communities, by developing in increasingly unstructured social environments, this activity ends up promoting an individualism that progressively deteriorates community values. This experience shows us how community-based tourism requires the prior strengthening of community structures and the implementation of an organizational system of collective control of the benefits derived from this activity.